The Bromodomain Protein 4 Contributes to the Regulation of Alternative Splicing - Sheetal Uppal; Anne Gegonne; Qingrong Chen; Petria S. Thompson; Dan Cheng; Jie Mu; Daoud Meerzaman; Hari S. Misra; Dinah S. Singer (Cell Reports, 2019)
Summary: The bromodomain protein 4 (BRD4) is an atypical kinase and histone acetyl transferase (HAT) that binds to acetylated histones and contributes to chromatin remodeling and early transcriptional elongation. During transcription, BRD4 travels with the elongation complex. Since most alternative splicing events take place co-transcriptionally, we asked if BRD4 plays a role in regulating alternative splicing. We report that distinct patterns of alternative splicing are associated with a conditional deletion of BRD4 during thymocyte differentiation in vivo. Similarly, the depletion of BRD4 in T cell acute lymphoblastic leukemia (T-ALL) cells alters patterns of splicing. Most alternatively spliced events affected by BRD4 are exon skipping. Importantly, BRD4 interacts with components of the splicing machinery, as assessed by both immunoprecipitation (IP) and proximity ligation assays (PLAs), and co-localizes on chromatin with the splicing regulator, FUS. We propose that BRD4 contributes to patterns of alternative splicing through its interaction with the splicing machinery during transcription elongation. : The bromodomain protein 4 (BRD4) is an important regulator of both normal development and tumorigenesis, regulating chromatin organization and transcription. Uppal et al. report that BRD4 also regulates alternative splicing: distinct patterns of alternative splicing are associated with depletion of BRD4 in T cell acute lymphoblastic leukemia (T-ALL) cancer cells and during thymocyte differentiation in vivo. Keywords: BRD4, alternative splicing, thymocyte differentiation, FUS, BET, AML